2013
DOI: 10.1371/journal.pone.0074596
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Mechanism of Inhibin α-Subunit Gene in Mouse Anterior Pituitary Cells by RNA Interference

Abstract: Inhibin, a member of the transforming growth factor-β [TGF-β] superfamily, is a suppressor of follicle-stimulating hormone [FSH] release through pituitary–gonadal negative feedback loop to regulate follicular development. In this study, Inhibin α-subunit [Inha] gene was knocked down successfully in mice primary anterior pituitary cells at both transcriptional and translational levels by RNAi-Ready pSIREN-RetroQ-ZsGreen Vector mediated recombinant pshRNA vectors. The results indicated that inhibin silencing sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 39 publications
0
18
0
2
Order By: Relevance
“…Inhibin primarily provides negative feedback regulation of FSH production. Inha knock‐out rats exhibited reduced expression of TGFBR3 , which disrupted inhibin‐TGFBR3 signaling and therefore increases the secretion of FSH in the rat anterior pituitary cells (Han et al, ). Also, although Inhbb expression was up‐regulated after Inha silencing, the secretion of Inhibin β is still decreased (Han et al, ), indicating how important their co‐production is.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibin primarily provides negative feedback regulation of FSH production. Inha knock‐out rats exhibited reduced expression of TGFBR3 , which disrupted inhibin‐TGFBR3 signaling and therefore increases the secretion of FSH in the rat anterior pituitary cells (Han et al, ). Also, although Inhbb expression was up‐regulated after Inha silencing, the secretion of Inhibin β is still decreased (Han et al, ), indicating how important their co‐production is.…”
Section: Discussionmentioning
confidence: 99%
“…Inha knock‐out rats exhibited reduced expression of TGFBR3 , which disrupted inhibin‐TGFBR3 signaling and therefore increases the secretion of FSH in the rat anterior pituitary cells (Han et al, ). Also, although Inhbb expression was up‐regulated after Inha silencing, the secretion of Inhibin β is still decreased (Han et al, ), indicating how important their co‐production is. Interestingly, inhibin vaccines that attenuate its activity resulted in higher fertility and ovulation rates in sheep, cattle, and rats (Dan, Liu, Han, Liu, & Yang, ; Han et al, ; Takedomi et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that Cyclin E is required for cells to transit from G1 to S phase (Liszewska, Rekawiecki, & Kotwica, 2005). Bcl-2 is an inhibitor of apoptosis, and its expression level determines the apoptotic fate of various cells (Han et al, 2013;Liszewska et al, 2005). Caspase-3 has been shown to promote cell apoptosis in most cells, and its activation often serves as an irreversible apoptotic signal (Mruk & Cheng, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Caspase‐3 has been shown to promote cell apoptosis in most cells, and its activation often serves as an irreversible apoptotic signal (Han et al. ). In this study, we found Caspase‐3 mRNA levels to be significantly upregulated upon overexpression of CEBP β .…”
Section: Discussionmentioning
confidence: 99%